Transthoracic Biopsy Causes Massive Subcutaneous Emphysema in a Low Risk Patient - Simsek, Fikri Selcuk; Dag, Yusuf (Premchand Shantidevi Research Foundation, 2016)
Subcutaneous Emphysema (SE) can be defined as air leakage under skin from the respiratory or gastrointestinal system. It is frequently accompanied by pneumomediastinum. Thoracentesis, image-guided lung biopsies, pulmonary diseases and therapies resulting in necrosis can cause this pathology. The risk of pneumothorax and SE increased with the distance of the lesion to the pleura, and small size of the lesion. Although, our patient had low risk for SE, there were minimal pneumothoraces and massive SE. We consider that tumour necrosis and subcutaneous tissue may be related via transthoracic biopsy and this leads to massive SE.
Keywords: Emphysema; Lung cancer; Pneumothoraces